2016
DOI: 10.2131/jts.41.459
|View full text |Cite
|
Sign up to set email alerts
|

Acute biomarker panel changes associated with amphotericin B nephrotoxicity in female Sprague-Dawley rats

Abstract: -To date, eight next-generation urinary protein kidney safety biomarkers have been qualified to enable monitoring for subclinical drug-induced kidney injury (DIKI) in rat preclinical studies; however, most DIKI biomarker studies have included only male rats. The objective of this study was to assess the utility of novel DIKI biomarkers, including but not limited to urinary total protein, albumin, cystatin C and osteopontin in female Sprague-Dawley rats (8/group) that received repeated intravenous injections of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“…In contrast, another study found no relevant alteration in the levels of Cys C, even when Saúde Meio Ambient. v. 10, p. 141-157, 2021 ISSNe 2316-347X histopathological analysis confirmed the occurrence of AKI, after the intravenous administration of AB for 10 days 46 .…”
Section: Cystatin C (Cys C)mentioning
confidence: 73%
“…In contrast, another study found no relevant alteration in the levels of Cys C, even when Saúde Meio Ambient. v. 10, p. 141-157, 2021 ISSNe 2316-347X histopathological analysis confirmed the occurrence of AKI, after the intravenous administration of AB for 10 days 46 .…”
Section: Cystatin C (Cys C)mentioning
confidence: 73%
“…In contrast, another study found no relevant alteration in the levels of Cys C, even when Saúde Meio Ambient. v. 10, p. 45-62, 2021 ISSNe 2316-347X histopathological analysis confirmed the occurrence of AKI, after the intravenous administration of AB for 10 days 46 .…”
Section: Cystatin C (Cys C)mentioning
confidence: 73%
“…Until 2008, the eight fully qualified urinary protein DIKI biomarkers had not been systematically investigated in AmpB-treated rats (Thukral et al 2005). Hence, McDuffie et al (2016) demonstrated the value of early elevations in Ur CLU, Ur NGAL, Ur ALB, Ur CYS C, Ur TP, Ur KIM-1, and Ur OPN for detecting subclinical AmpB nephrotoxicity in female SD rats, thereby providing the basis for inclusion of female rats on a case-by-case basis in nonclinical toxicology studies designed to investigate DIKI. Besides expected AmpB binding to tubular epithelial cells and subsequent swelling and lysis/increased tubular permeability and tubular dysfunction, the nature of DIKI in female SD rats remains unclear.…”
Section: The Evolution Of Kidney Safety Biomarkers—ampb Nephrotoxicitmentioning
confidence: 95%